THE RIGHT OF SPECIAL NEEDS TO HOLD PUBLIC OFFICE IN THE IRAQI LEGISLATION - Dr. Rasha Shakir Hamid , Dr. Khalid AbdulameerAbboodi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Researching the rights of special needs in the Iraqi legislation in general, and their right to assume public office in particular, is one of the most important topics that deserve research, especially since the Iraqi legislation has responded only relatively to what is stipulated in international standards related to the rights of this group of Society. The Convention on the Rights of Persons with Disabilities stipulated in Article (5) the principle of equality and non-discrimination. By that, it had followed the path of the Universal Declaration of Human Rights (Article/ 2, 25) as well as the International Covenant on Civil and Political Rights (Article/ 24), the Covenant of the International Conference on Economic, Social, and Cultural Rights (Article/ 10), and the Convention on the Rights of the Child (Article/ 2) ratified by the Republic of Iraq. The 2005 Iraqi constitution has explicitly and clearly indicated in Chapter Two of the section on Rights and Freedom, the principle of equality and non-discrimination among all Iraqis in rights and duties before the law, including persons with disabilities who possess all the rights and who bear the same duties without discrimination.